Motion of Tympanic Membrane in Guinea Pig Otitis Media Model Measured by Scanning Laser Doppler Vibrometry - Wang, Xuelin (Hear Res, 2016)
Otitis media (OM) is an inflammatory or infectious disease of the middle ear. Acute otitis media (AOM) and otitis media with effusion (OME) are the two major types of OM. However, the tympanic membrane (TM) motion differences induced by AOM and OME have not been quantified in animal models in the literature. In this study, the guinea pig AOM and OME models were created by transbullar injection of Streptococcus pneumoniae type 3 and lipopolysaccharide, respectively. To explore the effects of OM on the entire TM vibration, the measurements of full-field TM motions were performed in the AOM, OME and untreated control ears by using scanning laser Doppler vibrometry (SLDV). The results showed that both AOM and OME generally reduced the displacement peak and produced the traveling-wave-like motions at relatively low frequencies. Compared with the normal ear, OME resulted in a significant change of the TM displacement mainly in the inferior portion of the TM, and AOM significantly affected the surface motion across four quadrants. The SLDV measurements provide more insight into sound-induced TM vibration in diseased ears.